Effects of Gaps Between Side-Walls and 60∘ Ribs on the Heat Transfer and Rib Induced Secondary Flow Inside a Stationary and Rotating Cooling Channel - Robert Kiml; Sadanari Mochizuki; Akira Murata (International Journal of Rotating Machinery)
The present study investigates the effects of gaps between the side-walls and 60∘ ribs on the local heat transfer distribution between two consecutive ribs. The heat transfer and flow visualization experiments were carried out inside a straight rib-roughened duct with the ribs mounted on two opposite side walls with and without the gaps. The results showed that the existence of the gaps appreciably enhances the Nu in the area between two consecutive ribs. It is caused by (1) the introduction of the fresh air through the gaps into this region, and (2) the improvement of the three-dimensional flow structure in the area between the two ribs.